How representative are social partners in Europe? The role of dissimilarity - Marta Martínez Matute; Pedro S. Martins (Global Labor Organization (GLO), 2020)
Social partners (trade unions and employers' associations) shape labour institutions and economic and social outcomes in many countries. In this paper, we argue that, when examining social partners' representativeness, it is important to consider both affiliation and dissimilarity measures. The latter concerns the extent to which affiliated and non- affiliated firms or workers are distributed similarly across relevant dimensions, including firm size. In our analysis of European Company Survey data, we find that affiliation and dissimilarity measures correlate positively across countries, particularly in the case of employers' associations. This result also holds across employers' associations when we use firm population data for Portugal. Overall, we conclude that higher affiliation rates do not necessarily equate to more representative social partners as they can involve greater dissimilarity between affiliated and non-affiliated firms.
Keywords: J50; J23; L22; 330; Employers' Associations; Social Dialogue; Collective Bargaining